Diagnóstico ambiental de veredas na bacia do rio Uberabinha: qualidade de água e sedimentos - Faxina, Rudmir Rogerio de Camargo (2019)
The Triângulo Mineiro region of Minas Gerais in Brazil had a great population growth in the last decades, resulting in losses of biodiversity in the Cerrado biome. The Cerrado wetlands, one of the main phytophysiognomies that represents the birthplace of water sources have been suffering from the growing demand for water and space, both in the urban and rural areas. These areas form a vegetation complex characterized by the occurrence of hydromorphic soils, with groundwater table and the buritis (Mauritia flexuosa) as arboreal symbol. These zones are considered as permanent preservation areas, therefore, their limits, natural vegetation and quality of water resources must be preserved. Given the environmental impacts that affect areas of great fragility such as the Cerrado wetlands, this study aimed to evaluate the quality of water and sediment in five wetlands near the city of Uberlândia/MG, being three localized in rural areas and two urban. Analysis of twenty-four physical-chemical parameters and metallic elements were carried out over a period of twelve months covering rainy and dry seasons. The sampled data were submitted to different statistical methods to evaluate the chemical composition of water and sediments and area classification. The metallic elements in the sediments were important for the quality analysis, since they showed that even with a similar soil class, the wetlands were differentiated due to the variations in the uses and occupations of the soil in the region. Principal component and cluster analysis also showed that the conservation of natural vegetation in veredas and surrounding areas may contribute to water quality. The chemical attributes evaluated revealed great differences in water quality between urban and rural areas. The area with the highest number of parameters in non-conformity was one of the urban wetlands. Correlation tests assured the detection of external, anthropogenic and natural sources of some elements (Ca, Cd, K, Na, Mg and V), especially in the rainy season. This study also clearly showed that veredas with urbanization nearby, consequently has more interventions and exert more pressure on water quality than in environments with preserved natural vegetation.